THE IMPACT OF ISLAMIC MONETARY OPERATIONS AND AGGREGATE FINANCING ON ECONOMIC GROWTH IN INDONESIA (2010-2020) - Madani, Adinda; Widiastuti, Tika (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
Islamic monetary operation policies are regulated to increase the effectiveness in facing economic developments, especially the monetary sector. The working mechanism of the Islamic monetary operation up to its impact on the development of the national economy illustrates the monetary policy transmission carried out by Bank Indonesia. The purpose of this study is to analyze the effects of Bank Indonesia Sharia Certificate (SBIS), Bank Indonesia Sharia Deposit Facility (FASBIS), Sharia Interbank Money Market (PUAS), and aggregate financing on Indonesia's economic growth in the period 2010 to 2020. This research method uses a quantitative approach with the analysis technique Vector Auto Regression (VAR) or Vector Error Correction Model (VECM) to see the long-term impact and shock response on certain variables. Using secondary data on the variables, it is obtained from the Indonesian Economic and Financial Statistics Bank Indonesia (SEKI-BI) and the Central Statistics Agency (BPS) for the period January 2010 to December 2020. This study found that the SBIS variable has a negative relationship with GDP. Meanwhile, the variables FASBIS, PUAS, and aggregate financing have a positive relationship with GDP. For the future, it can be used as input and consideration in policy making that will be determined in optimizing Islamic monetary policy in Indonesia. Further research that will discuss this topic should use Islamic monetary instruments that are more complete than Islamic open market operations and sharia standing facilities. As well as comparing with conventional monetary operation instruments as a comparison for Islamic monetary.